Inclusion Matters in Africa - Das, Maitreyi Bordia; Espinoza, Sabina Anne (World Bank, Washington, DC, 2019)
Africa has garnered global attention for its many achievements and its dynamism, and at the same time, it has taken the spotlight for its substantial challenges. As in other parts of the world, positive developments have been uneven in Africa. This report places the notion of social inclusion in an analysis of Africa’s achievements and challenges. Its interdisciplinary approach uses evidence to bring empirical weight to issues that are often debated through advocacy and contestation. It also contributes to the priority areas of a new regional strategy for the Africa region of the World Bank by focusing on women’s empowerment, digital technology, fragility, and climate change, among others. The report asks, in the wake of the advances Africa has made over the years, who is excluded, from what, how, and why. It then highlights what has been attempted in the quest of African countries for social inclusion. One of the main contributions of this report is that while grounded in the experience of African countries, it shows that Africa’s challenges in social inclusion are not unique or exceptional. It highlights examples of the remarkable innovations that abound in Africa and of the policy and programmatic movement towards social inclusion. It surmises that social inclusion must be based on a clear social contract that recognizes both the costs and benefits of policies and interventions towards social inclusion.